Hormone-Like Effects of 4-Vinylcyclohexene Diepoxide on Follicular Development - Cao, Lian Bao; Liu, Hong Bin; Lu, Gang; Lv, Yue; Leung, Chi Kwan; Du, Yan Zhi; Wang, Wu Ming; Xiong, Zhi Qiang; Su, Xian Wei; Li, Hong Jian; Chen, Zi-Jiang; Ma, Jin Long; et al. (Frontiers in Cell and Developmental Biology, 2020)
ABSTRACT Background: 4-vinylcyclohexene diepoxide (VCD) has long been considered as a hazardous occupational chemical that promotes ovarian failure. However, VCD is also used as a research compound to chemically induce animal models of premature ovarian insufficiency, and in related work we unexpectedly detected that VCD apparently exhibits both dose- and duration-dependent opposing, hormone-like effects on the maintenance of primordial follicle pool, follicle development, and ovulation induction. Results: We conducted experiments with cultured murine ovaries and did transplantation experiments using postnatal day (PD) 2 and PD12 mice, and found that low-dose (VCDlow), short-term exposure to VCD actually protects the primordial/primary follicle pool and improves the functional ovarian reserve (FOR) by disrupting follicular atresia. VCDlow inhibits follicular apoptosis and regulates the Pten-PI3K-Foxo3a pathway. Short-term VCD exposure in vivo (80mg/kg, 5 day) significantly increases the number of superovulated metaphase II (MII) oocytes, preovulatory follicles, and corpora lutea in middle-aged mice with diminished ovarian reserve (DOR). We demonstrate that low-dose but not high-dose VCD promotes aromatase levels in granulosa cells (GCs), thereby enhancing the levels of estradiol (E2) secretion. Conclusions: Our study illustrates a previously unappreciated, hormone-like action for the occupational "ovotoxin" molecule VCD and strongly suggests that VCDlow should be explored for its potential utility for treating human ovarian follicular development disorders, including subfertility in perimenopausal women.